Intra-examiner and Inter-examiner Reproducibility in Irregularity Index Measurements - Ersat Cem İrezli; Mücahid Faik Şahin; Rana Demir; Aslı Baysal (Galenos Yayinevi, 2019)
Objective:This study aimed to assess intra-examiner and inter-examiner reproducibility in irregularity index measurements.Methods:Twenty plaster casts of moderately crowded arches were randomly selected, and five contact point displacements (CPD) at lower anterior segment (through no. 33 to no. 43) were recorded using digital calipers on two different time points by three examiners to determine irregularity index (sum of five CPDs). To evaluate intra-examiner and inter-examiner differences, paired t-test and analysis of variance were used, respectively. Correlation analyses were performed between examiner pairs, and intra-class correlation coefficients (ICC) were determined. Statistical significance was set at p≤0.05.Results:Only a few of the repeated measurements of examiners showed significant differences (p≤0.05). All researchers were consistent in repeated measurements (p=0.000), and ICCs ranged between 0.916 and 0.986. For one CPD measurement, a statistically significant difference was detected among examiners (p=0.020). High correlation was found for inter-examiner repeatability (p<0.05), and ICCs ranged between 0.739 and 0.984. But when the difference of 1.5 mm among measurements was set as clinically relevant, the percentages of these values for repeated measures were 15%, 5%, and 45% for examiner 1, 2, and 3, respectively. These percentages were 25%, 80%, and 65% for examiner pairs.Conclusion:Irregularity index may be a misleading index to determine anterior alignment especially when measuring small CPD.